What the dog knows : the science and wonder of working dogs - Warren, Cat.x (New York : Simon & Schuster, 2015)
Explores the world of working dogs, as well as canine intelligence and training, as the author and her German shepherd, Solo, work with forensic anthropologists, detectives, and dog handlers to find the bodies of the missing.
The little prince of darkness -- Death and the dog -- Nose knowledge -- The birth of the body dog -- The shell game - - Distillations -- A spare rib -- Comfort me with bite work -- Into the swamp -- Cleverness and credulity -- All the world's a scenario -- The grief of others -- All the soldiers gone -- Running on water -- The perfect tool -- Grave work -- A second wind -- Wag.
"A Touchstone book."
Includes bibliographical references (pages 295-320) and index.
Keywords: Warren, Cat; Search dogs -- Anecdotes